Vestir a luta: a moda como veículo de sensibilização sobre a violência contra jovens negros no Brasil - Lima, Patrícia Mendonça (2019)
Presuming that fashion can be seen as a mirror of world social transformation, this study seeks to show how, in particular, the T-shirt could be used as a communication platform. The main objective is to disseminate information about the violence that, in Brazil, leads to the systematic death of young black people living in poor and peripheral communities; and sensitize the general population to this situation. This research is an exploratory investigation that was based on secondary statistical data taking into account qualitative factors. The product of this study proposes is a collaborative Web Platform, aligning with the program of Experience Design and Innovation Strategy. aims to promote awareness and discussion of events related to the theme, eventually reversing the result of selling their products to a movement of mothers who lost their children to violence. Beyond the academic field, this work intends to have an impact on society, as it promotes discussions, reinforces values such as diversity and social inclusion, establishes dialogue with different audiences and can generate income, highlighting - finally - the social and didactic roles of design